HISTORIA Y MITO: UNA NOVELA DESAPARECIDA DE MARGUERITE YOURCENAR, LES EMMURÉS DU KREMLIN - Vázquez de Parga y Chueca, María José (Anales de Filología Francesa, 1992)
In the second edition of the Nouvelles Orientales one tale was suppressed that had been published in the first edition of 1938: «Les Emmurés du Kremlinn. After its author, the tale had its origin in a Slav legend, but it resembles the story of the Seven Saints of Ephese. The cause of the suppression of the tale makes the subject of the present work. The only annotation done by the tale’s author on this subject, was that the tale would not be welcome and it wasn’t worth-while to retouch it. The reason that we find to be the cause of the suppression of the tale is its social message not fitting in 1963.